C53 DONOR–DERIVED CELL–FREE DNA (DD–CFDNA)–BASED ASSESSMENT OF CORONARY ALLOGRAFT VASCULOPATHY IN HEART TRANSPLANTED PATIENTS. (18th May 2022) - Bulfoni, M; Dralov, A; Ferrara, V; Marcon, B; D'Aurizio, F; Nalli, C; Di Nora, C; Sponga, S; Beltrami, A; Livi, U; Curcio, F
Abstract: Introduction: Cardiac Allograft Vasculopathy (CAV) is a leading cause of long–term graft dysfunction and failure after Heart Transplant (HTx). Early diagnosis is crucial to tailor therapeutic strategies. Despite advancements in cardiac imaging, the standard for CAV diagnosis remains coronary angiography. Donor–derived cell free DNA (dd–cfDNA) is a novel marker of graft injury in solid organ transplants. Elevations in dd–cfDNA levels may reflect CAV development during subclinical inflammation, thus it could represent a non–invasive method of surveillance for CAV rejection in apparently stable post–transplant patients. Given these premises, we decided to evaluate the potential of dd–cfDNA as alternative diagnostic biomarker for CAV. Materials and Methods: 31 blood samples from patients who underwent heart transplant at our institution in the last 10 years, were analyzed by Next Generation Sequencing (NGS) according to CareDx Alloseq protocol. The cfDNA was extracted starting from 2mL of plasma (Qiagen). Sequencing was performed on the Illumina Miseq platform. Troponin T (hs–TnT) and NT–proBNP (Brain Natriuretic Peptide) were measured by automated immunoassay analysers. All statistics were performed by STATA software and significance was set at p < 0.05. Results: Heart transplant recipients were divided into 2 groups: 16 patients with known CAV status and 15 patients who had not (no–CAV). No significant differences between the two populations were observed, aside from time from HTx (177.28± 84.99 months in CAV vs 93.20 ± 84.39 months in no–CAV; p = 0.033). A significant difference in dd–cfDNA fraction was found between CAV and no–CAV patients (p = 0.03); with mean values of 0, 41% e 0, 13%, respectively. Neither NT‐proBNP (p = 0.08) nor hs–TnT (p = 0.31) concentrations were significantly different between the two groups, but a positive correlation was found between the two biomarkers (r 0.6966; p = 0.0013). A trend of linear relationship emerged between cfDNA and NT‐proBNP levels (r 0.4155; p = 0.08). Conclusions: With this study, we demonstrated the feasibility of evaluating dd–cfDNA in long–term heart transplanted patients and its possible association with CAV development. Further investigations are warranted to explore a possible association between dd–cfDNA levels other circulating biomarkers and CAV progression. The definition of "homogeneous" subgroups of patients according to a "risk score" will allow to better manage their follow up and improve their prognosis.